2022
DOI: 10.1186/s12890-022-01885-4
|View full text |Cite
|
Sign up to set email alerts
|

A modified lung ultrasound score to evaluate short-term clinical outcomes of bronchopulmonary dysplasia

Abstract: Background Lung ultrasound (LUS) is a useful tool for assessing the severity of lung disease, without radiation exposure. However, there is little data on the practicality of LUS in assessing the severity of bronchopulmonary dysplasia (BPD) and evaluating short-term clinical outcomes. We adapted a LUS score to evaluate BPD severity and assess the reliability of mLUS score correlated with short-term clinical outcomes. Methods Prospective diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 44 publications
(41 reference statements)
2
20
0
Order By: Relevance
“…Subjects were enrolled in a prospective cohort study at the Children's Hospital of Fudan University from January 2017 to December 2019. A detailed description of the cohort has been previously described elsewhere 19 . To be eligible for the modified NICHD‐defined BPD classification, the included participants needed to be born at less than 32 weeks of gestational age.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subjects were enrolled in a prospective cohort study at the Children's Hospital of Fudan University from January 2017 to December 2019. A detailed description of the cohort has been previously described elsewhere 19 . To be eligible for the modified NICHD‐defined BPD classification, the included participants needed to be born at less than 32 weeks of gestational age.…”
Section: Methodsmentioning
confidence: 99%
“…Standardized respiratory care and BPD procedures were applied in routine clinical care. The protocol was described in our previous publication 19 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Sun et al evaluated the association between BPD severity and a modified Brat score which also included retro-hepatic and retro-splenic views obtained from subcostal scans. Although the modified score appeared to better correlate with BPD severity at 36 weeks than the classic one, its predictive capacity at 7-14 days of life was not explored (85). The two different scoring types (6 vs. 10 chest fields) have also been evaluated in a meta-analysis (84) which recommended using simpler one, since no significant betweenscores difference was detected in terms of BPD prediction.…”
Section: Lung Ultrasound Markers For Bpd Association or Predictionmentioning
confidence: 99%
“…A recent study in 2022 reported a new prediction method based on a modified lung ultrasound score. 122 The investigators modified the classical lung ultrasound score by including sagittal scans of the liver and spleen using a convex probe from the lower end of the ribs. 1,[123][124][125][126][127] These datapoints were potentially useful because CLD affects the posterior and lower part of the lung more than the anterior region.…”
Section: Evaluation Of Chronic Lung Diseasementioning
confidence: 99%